2013
DOI: 10.1016/j.jalz.2013.04.353
|View full text |Cite
|
Sign up to set email alerts
|

O4–04–02: Prevalence studies of dementia in mainland China, Hong Kong and Taiwan: A systematic review and meta‐analysis

Abstract: Background: Many studies have considered the prevalence of dementia in mainland China, Hong Kong and Taiwan. However, area level estimates have not been produced. This study examines area differences across mainland China, Hong Kong and Taiwan adjusting for the effect of methodological factors with the aim of producing estimates of the numbers of people with dementia in these areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…2 A Chinese systematic review that did not fully incorporate methodological changes reported substantial increases in prevalence over time, 10 whereas another review that included methodological changes found no significant increase in dementia prevalence. 9 Considering the clear shift of the threshold of clinical dementia toward a milder stage according to clinical approaches, only objective measures, such as CIWD, are comparable for examination of secular trends.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A Chinese systematic review that did not fully incorporate methodological changes reported substantial increases in prevalence over time, 10 whereas another review that included methodological changes found no significant increase in dementia prevalence. 9 Considering the clear shift of the threshold of clinical dementia toward a milder stage according to clinical approaches, only objective measures, such as CIWD, are comparable for examination of secular trends.…”
Section: Discussionmentioning
confidence: 99%
“…R ecent epidemiological studies have reported an unexpected decline in prevalence and incidence rates of dementia or cognitive impairment in older people born later in the first half of the 20th century (four prevalence studies, [1][2][3][4] four incidence studies [5][6][7][8] from Western Europe and United States). In Asia, no significant reduction was reported in a review of 75 dementia prevalence studies 9 and an increase in another. 10 Some studies have reported stable trends, [11][12][13] and there are contradictory results from the United States 14 and Japan.…”
mentioning
confidence: 91%
“…The age-adjusted prevalence of all-cause dementia in a nationwide survey conducted in Taiwan was 8.04% [1]. In Taiwan, the projected number of people with dementia (aged 65 years) is 0.15 million, and this number is expected to reach 0.21 million by 2020 [2]. Current treatment options for Alzheimer's disease (AD) available in Taiwan include cholinesterase inhibitors (ChEIs), such as rivastigmine, donepezil, and galantamine, or the N-methyl-D-aspartate receptor antagonist, memantine [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most are simply obtained by applying current prevalence rates to the projected Chinese population Alzheimer's Disease International and Alzheimer's Australia, 2014;Li et al, 2015), or aggregated with other developing countries (Ferri et al, 2005). Furthermore, some projections focus on elderly formally diagnosed with AD or dementia (Ferri et al, 2005;Wu et al, 2013;Alzheimer's Disease International and Alzheimer's Australia, 2014), without distinguishing degree of CI, which is strongly related to distinct behavioral features and care needs.…”
Section: Introductionmentioning
confidence: 99%